Parental Behavior on the Growth Period of Deciduous Teeth and Permanent Teeth in Children in Central Aceh - Teuku Salfiyadi; Cut Aja Nurskin; Ummul Khaira; Nadhiratun Ramadhani; Wahyu Maisarah; Fatteriawati Fatteriawati; Darmila Darmila; Reca Reca (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
The purpose of this study was to determine the relationship between parental behavior and the growth of deciduous and permanent teeth in children. The method in this research is quantitative with a cross-sectional approach. While the sample is the community who visited the Pegasing Health Center, Pegasing District, Central Aceh Regency as many as 35 people who have children. The results showed that parents' knowledge of the growth period of deciduous and very low teeth was 64%, while those with good knowledge were 36%. While the attitude of parents to the period of growth of children's teeth is in the less category as much as 62.8% and in the good category at 37.2%. Meanwhile, the actions of parents during the child's teething period were also in the less category with a percentage of 55.1% while those who had good actions were 44.9%. This study concludes that the knowledge of parents' attitudes and actions towards the growth period of deciduous and permanent teeth at the Pegasing Public Health Center in Central Aceh still needs to be improved so that parents will have more knowledge about the importance of the child's teething period. So there is a relationship between parental behavior on the growth period of deciduous teeth and permanent teeth in children, parental behavior is very influential on the health and growth process of children's teeth. The conclusion is that the behavior of parents has a great influence on children's dental health education so the knowledge, attitudes, and actions of good parents will contribute to the development of dental health education.